If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + 13 = 10 + -7 Reorder the terms: 13 + 9a = 10 + -7 Combine like terms: 10 + -7 = 3 13 + 9a = 3 Solving 13 + 9a = 3 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 9a = 3 + -13 Combine like terms: 13 + -13 = 0 0 + 9a = 3 + -13 9a = 3 + -13 Combine like terms: 3 + -13 = -10 9a = -10 Divide each side by '9'. a = -1.111111111 Simplifying a = -1.111111111
| -8x-26=-5x+28 | | -(x+1)=4(1+x) | | 29=-8t+3 | | -9x-12=-8x+9 | | -8x-42=18-5x | | (19.95)x+3=x | | 3x-12(+676)=200 | | 84-3x=66 | | 3+5(4x+6)=2x+3 | | 5y+2=9 | | h(t)=-.05t^2+3t | | 2x+1=-(-9) | | 5(2x-4)=30 | | -9a-8a= | | -16minusk=-7 | | 19-(x+6)=6x-8 | | 2f+5=17 | | 9(x-9)+3=-78 | | 10t+.15t^2=-900 | | 25+15+18+P*.25=20 | | 22x^2+34x-100= | | 3x+5(-43)=20 | | 4x^2+20x-144=0 | | a^2+10=28 | | -8-42=18-5x | | x^2+9x+15=0 | | 22x^2+3x-100= | | 7y^2-10y+3=0 | | x^4-3x^2=-2 | | -3v+4=-v+8 | | 8y*-5y+12-13y*-5y+2= | | (-2)(-2)x=16 |